2013
DOI: 10.1164/rccm.201303-0539oc
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Effort Causes Occult Pendelluft during Mechanical Ventilation

Abstract: Spontaneous breathing effort during mechanical ventilation causes unsuspected overstretch of dependent lung during early inflation (associated with reciprocal deflation of nondependent lung). Even when not increasing tidal volume, strong spontaneous effort may potentially enhance lung damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
331
1
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(362 citation statements)
references
References 25 publications
5
331
1
12
Order By: Relevance
“…However, in animals with severe lung injury, spontaneous breathing worsened lung injury, suggesting that muscle paralysis might be more protective for injured lungs by preventing injuriously high P L . In another experimental study, Yoshida et al 68 found that spontaneous breathing caused pendelluft during early inflation, which was associated with more negative local P pl in dependent lung regions versus non-dependent regions. This occurred despite limitation of V T to Ͻ 6 mL/kg.…”
Section: Spontaneous Breathing and Pressure-targeted Ventilationmentioning
confidence: 95%
“…However, in animals with severe lung injury, spontaneous breathing worsened lung injury, suggesting that muscle paralysis might be more protective for injured lungs by preventing injuriously high P L . In another experimental study, Yoshida et al 68 found that spontaneous breathing caused pendelluft during early inflation, which was associated with more negative local P pl in dependent lung regions versus non-dependent regions. This occurred despite limitation of V T to Ͻ 6 mL/kg.…”
Section: Spontaneous Breathing and Pressure-targeted Ventilationmentioning
confidence: 95%
“…Consequently, the tidal change in transpulmonary pressure (tidal lung stress) at dependent lung became greater than at the middle lung. Volume control ventilation hence didn't prevent high regional lung stress and injurious inflation pattern (regional gas distribution) such as "pendelluft" reported in pressure control ventilation (23). This important finding advanced our knowledge that the dependent region of injured lung can be overstretched by spontaneous effort even when the tidal volume (global lung stretch) has been limited at 6 mL/kg.…”
Section: New Messages From Yoshida's Studymentioning
confidence: 87%
“…Although we do not know the precise mechanisms, this strongly suggested a deleterious effect of spontaneous breathing under mechanical ventilation. Spontaneous breathing could increase ventilation by breath stacking [11] or reverse triggering [12], but Yoshida et al also showed that, without increasing tidal volume, spontaneous ventilation with a high respiratory drive could induce an internal redistribution of the inspired tidal volume generating local injurious forces [13]. Recently, we proposed the concept of patient self-inflicted lung injury (P-SILI) to describe all these conditions where a high respiratory drive induced by local lung injury could result in global or regional pressure changes susceptible to aggravating the initial lung injury [14].…”
Section: Evidence Of Ventilation-induced Lung Injury During Spontaneomentioning
confidence: 99%